2020
DOI: 10.3390/su12062165
|View full text |Cite
|
Sign up to set email alerts
|

Does an Emissions Trading Policy Improve Environmental Efficiency? Evidence from China

Abstract: An emissions trading system is a market instrument for pollution control that has been used in China for many years. The Ministry of Environmental Protection of China has approved the implementation of emissions trading pilot projects in 11 provinces since 2007, yet the effectiveness of the policy has not been comprehensively estimated. With panel data from 29 provinces and cities in China between 2003 and 2012, this study uses the data envelopment model-slack based measurement (DEA-SBM) method to measure envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…For instance, companies are directing substantial investments into the development of alternative fuel vehicles, including electric, hybrid, and hydrogen fuel cell cars, to meet the burgeoning demand for ecofriendly transportation (Zhang et al, 2020). These pioneering technologies necessitate significant research and development investments, which may impact a firm's short-term financial performance but can yield a sustainable competitive advantage over time (Kim, Kim, & Park, 2021;Kim, Lee, et al, 2021).…”
Section: Innovationmentioning
confidence: 99%
“…For instance, companies are directing substantial investments into the development of alternative fuel vehicles, including electric, hybrid, and hydrogen fuel cell cars, to meet the burgeoning demand for ecofriendly transportation (Zhang et al, 2020). These pioneering technologies necessitate significant research and development investments, which may impact a firm's short-term financial performance but can yield a sustainable competitive advantage over time (Kim, Kim, & Park, 2021;Kim, Lee, et al, 2021).…”
Section: Innovationmentioning
confidence: 99%
“…As the policy advances, the research sample has extended in time and space, and inconsistencies in research findings emerge. At the regional level, some scholarly studies have pointed out that EST can not only effectively promote SO 2 emission reduction [12], green development [28] in the pilot provinces, improving environmental efficiency [29] and raise environmental awareness in the surrounding areas [16]. On the contrary, Bingqing Hou et al (2020) showed that ETS implementation hurts green development based on urban panel data [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, this subsection discusses the sustainability of the usage of shared economy, which shows many controversies, including the feasibility and sustainability of sharing economy (Zhang et al 2020a ). It also discusses the way shared economy promotes environmental growth as well as quality of life.…”
Section: Literature Reviewmentioning
confidence: 99%